OATHS IN THE QUR’ÂN: BINT AL-SHÂTI’’S LITERARY CONTRIBUTION - Burhan SÜMERTAŞ (Fırat University, 2019)
“Nay, I swear by the places of the stars. That this is indeed a Quran most honourable. That this is indeed a Quran most honourable.” (Vâkıa, 56/75-77). Oaths (aqsâm, sing. qasam) are one of the most widespread and effective ways of drawing attention or eliciting trust in interpersonal and intercultural communications. As a theological and literary device, the Qur’ân has used oaths frequently with a view to appeal to its target audience. However, the most popular Muslim exlanations fort he Qur’ân’s use of oaths, apparently, are theological, namely, that they either point to the existence and majesty of the Creator (bâri’/sâni’) the object’s utility and benefit (manfa’ah), or its virtue and glorification (fadîlah/ta’zîm). Although Muslims have treated the literary aspect of the Qur’ân exhaustively the literary implications of oaths seem not to have been explored rigorously. Not a comparative study, this essay will explore the “other” least known theories and explanations of Bint al-Shâti’ (d. 1420/1999) on oaths, while also pointing out the Qur’ân’s effective use of such oaths. Unlike most Muslim scholars, Bint al-Shâti’ believes that most of the Qur’ân’s oaths are meant for “artistic illustration” (al-bayân al-fannî). She devotes many pages to elaborating upon this in her al-Tafsîr al-Bayânî as well as in her al-I’câz al-Bayânî. Using Jalâl al-Dîn al-Suyûtî (d. 911/1505) to epitomize the traditional approach, I hope to provide explanation to a part of what appears in his al-Itqân. As fascinating literary explanations, this study will elaborate them and highlight their communicative significance.